Science Learning Motivation Among Students at Junior and Senior High Schools in Sungai Penuh: A Comparative Study - Satrianti, Elza; Pranata, Ogi Danika; Tiara, Tiara (Jurnal Pijar Mipa, 2024)
Student motivation in science learning has significantly changed during the pandemic. Consequently, it is crucial to trace how student motivation in science has evolved. This study uses a descriptive and comparative research approach to obtain a general overview of students' science learning motivation and compare the levels of student learning motivation, providing a comprehensive overview of student motivation at different educational levels. The total sample size for this study is 104 students, selected using purposive sampling techniques from two schools, junior high school (madrasa) 1 and senior high school 1 Sungai Penuh. A questionnaire on students' motivation for learning science, adapted from a previous study, was utilized to collect student motivation data. Student responses were converted into quantitative data using a Likert Scale of 1 to 5. The collected data were processed and analyzed using descriptive and Mann-Whitney U-test statistics. The results reveal a significant difference in the motivation for learning science between senior high school 1 and junior high school (madrasa) 1 students. The group of students from senior high school 1 exhibited a higher level of science learning motivation than those from junior high school (madrasa) 1. When comparing indicators, no significant differences were found in the motivation of students from junior high school (madrasa) 1 and senior high school 1 Sungai Penuh for learning goal orientation, self-efficacy, and self-regulation. The difference in motivation indicators was only significant in task value. These findings can guide classroom teachers in refocusing their teaching practices and assessing the effectiveness of intervention programs. Exploring other factors across various subjects and school levels is also recommended to gain a more comprehensive understanding of the variations in student learning experiences.